Eksplorasi Etnomatematika ada Rumah Adat Tana Mbumbu Masyarakat Watumite Kecamatan Nangapanda Kabupaten Ende dan Integrasinya dalam Pembelajaran Matematika - Selviana Da Pion; Wara Sabon Dominikus; Aleksius Madu (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Tana Mbumbu is a traditional house located in Watumite. The Tana Mbumbu traditional house also serves as a place to resolve customary problems that occur among the community. This study aims to describe ethnomathematics and mathematical concepts in the Tana Mbumbu traditional house and develop learning tools related to mathematical concepts found in the Tana Mbumbu traditional house. This study uses qualitative research with an ethnographic approach. The research instruments used consist of the researcher as the main instrument and supporting instruments, namely observation sheets, interview guidelines, and documentation. Data analysis was carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The validity of this research data uses source triangulation. The results of the study indicate that the Tana Mbumbu traditional house has ethnomathematics that include calculating, measuring, localizing, designing, and explaining which reflect the concepts of counting, multiplication, non-standard measurement, floor plan and cardinal directions, geometry, linear equations, and similarity. These concepts can be used as a basis for developing learning tools in the future.